2016
DOI: 10.1051/0004-6361/201527806
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the properties of the X-shaped bulges of NGC 4710 and the Milky Way with MUSE

Abstract: Context. Our view of the structure of the Milky Way and, in particular, its bulge is obscured by the intervening stars, dust, and gas in the disc. While great progress in understanding the bulge has been achieved with past and ongoing observations, the comparison of its global chemodynamical properties with respect to those of bulges seen in external galaxies has yet to be accomplished. Aims. We used the Multi Unit Spectroscopic Explorer (MUSE) instrument installed on the Very Large Telescope (VLT) to obtain s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 60 publications
1
19
0
Order By: Relevance
“…We obtained spectral and imaging coverage of NGC 4710 using the Multi Unit Spectroscopic Explorer (MUSE) instrument installed on the Very Large Telescope (VLT). The observations were taken as part of the MUSE Science Verification observing run in June 2014 and their details can be found in the study of the kinematics of NGC 4710 presented in Gonzalez et al (2016). MUSE (Bacon et al 2010) is an optical wide-field integral-field spectrograph that uses the image slicing technique to cover a field of view (FOV) of 1 × 1 in wide-field mode resulting in a spatial sampling of 0.2 × 0.2 spaxels and resolving power from R ∼ 2000 at 4600Å to R ∼ 4000 at 9300Å .…”
Section: Observationsmentioning
confidence: 99%
See 4 more Smart Citations
“…We obtained spectral and imaging coverage of NGC 4710 using the Multi Unit Spectroscopic Explorer (MUSE) instrument installed on the Very Large Telescope (VLT). The observations were taken as part of the MUSE Science Verification observing run in June 2014 and their details can be found in the study of the kinematics of NGC 4710 presented in Gonzalez et al (2016). MUSE (Bacon et al 2010) is an optical wide-field integral-field spectrograph that uses the image slicing technique to cover a field of view (FOV) of 1 × 1 in wide-field mode resulting in a spatial sampling of 0.2 × 0.2 spaxels and resolving power from R ∼ 2000 at 4600Å to R ∼ 4000 at 9300Å .…”
Section: Observationsmentioning
confidence: 99%
“…Thus the simulation was able to follow the chemical evolution of all stellar populations. Gonzalez et al (2016) used the MUSE observations of NGC 4710 to map the kinematics of its bulge. They used the Penalised Pixel Fitting routine pPXF 1 (Cappellari & Emsellem 2004) to evaluate the galaxy's stellar kinematics by fitting the Single Stellar Population (SSP) MILES library of Vazdekis et al (2010) to the observed spectra in pixel space using a maximum penalised likelihood method.…”
Section: Simulationmentioning
confidence: 99%
See 3 more Smart Citations